Application of Augmented Reality in Geometry Learning in Increasing Student Learning Motivation - Maira Nevarini; Riza Agustiani; Atika Zahra (Journal of Curriculum and Pedagogic Studies (JCPS), 2023)
ICT-based learning media is urgently needed to increase student motivation in learning, especially learning mathematics in flat material. The learning media used is Augmented Reality. Augmented Reality is defined as a technology that combines the real world with the virtual world, is interactive in real time, and is in the form of three-dimensional animation. This type of research is research design research type validation study qualitatively. Students' interest in learning that utilizes technology directly can be seen from their enthusiasm when explained about the barcode which contains augmented reality in the form of the Musi 6 Palembang bridge. Based on the research process that was carried out both during the pilot experiment and teaching experiment, the researchers saw that the enthusiasm of the students was not much different. In addition to increasing the enthusiasm of students, it turns out that there is a barcode containing augmented reality in the form of the Palembang 6 musi bridge about the activities students will be working on, which also helps students understand what they are doing. With the help of explanations from these videos the teacher makes it easier and saves more time because students are not confused when carrying out the activities given